Coram Deo in Christian Religious Education: A Literature Review on Integrating the Christian Worldview into 21st-Century Pedagogical Practice - Nella Mariana Panjaitan (PT FORMOSA CENDEKIA GLOBAL, 2026)
The development of education in the twenty-first century presents significant challenges to Christian Religious Education (CRE), particularly when learning processes become increasingly driven by academic performance and pragmatic outcomes, while the formation of faith and character is often overlooked. This article revisits the concept of Coram Deo living before the face of God as a theological framework that can guide pedagogical practice in CRE. This study employs a literature-review method by examining books and scholarly articles, particularly from the past five years, related to the Christian worldview, faith-learning integration, and spiritual formation. The data were analyzed thematically to identify major contributions, gaps, and possibilities for developing a pedagogical model. The findings indicate that Coram Deo does not merely emphasize individual spirituality; rather, it shapes how learners understand themselves, the world, and their vocation. CRE is therefore understood not simply as the transmission of religious knowledge, but as a process of faith formation that engages cognitive, affective, and spiritual dimensions in a holistic manner. This article proposes a Coram Deo Pedagogical Model that integrates the biblical narrative of Creation–Fall–Redemption–Restoration into instructional stages, and highlights collaboration among school, family, and church as a formative ecosystem.